EKSISTENSI KRITIK MATAN MASA AWAL: Membaca Temuan dan Kontribusi Jonathan Brown - A Amrulloh (Kontemplasi: Jurnal Ilmu-Ilmu Ushuluddin, 2016)
This article is a reading of the idea of Jonathan Brown, a scholar of Western-Muslim who paid attention to the study of hadith, as stated in one of his writings, “How We Know Early Hadith Critics Did Matan Criticism and Why It’s So Hard to Find “. In his writings, Brown discovered samples of explicit criticisms made by critics matan hadith early. After analyzing the samples, he later concluded that the critics hadith early criticism matan has applied to test the authenticity and validity of hadith Prophet. According to him, the criticism sanad and matan criticism applied along and in line. However, because of certain reasons-one of which is the tension between traditionalists and rationalists that time, the application of the early criticism matan framed and wrapped in the language of criticism sanad. This reading was intended to reveal the findings of Brown’s early criticism of honor, and then analyze it to know its contributions in the development of critical studies hadith, especially matan criticism.Keywords: Hadith, sanad criticism, matan criticism, Jonathan Brown